FUNDAMENTALISME: SEMANGAT MENJAGA KEMURNIAN ISLAM KRITIK KONSTRUKTIF WILLIAM MONTGOMERY WATT - Muhammad Taufik (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2015)
As a popular issue recently, the fundamentalism is more understood as a movement within a sect, school or religion that striving to return to what they believe as the fundamentals or the foundations. The groups followed this idea are often involved conflict with another groups even within their own religion for the reason that their missions are to get rid ofthe impurities ofreligion. In positive meaning, "fundamentalist" is a term referring to a movement that revival or purify the religion. As stated in this writing, in Islam this fundamentalist movement is also increased, as a study by W. Montgomery Watt.According to Watt the Islamic fundamentalist group is the Muslim group that accepting traditional world view and making an effort to preserve it completely. More over according to Watt, the emerging of fundamentalism in Islam is a kind of encounter to what they call as "the enemy oflslam" in this case is the West. Beside of that, Watt articulated that traditional Muslims are also decline pluralism as a necessity.